Vascular tree-in-bud sign in Pulmonary Tumour Thrombotic Microangiopathy (PTTM): CT findings for a difficult radiological early antemortem diagnosis - Cozzi, Diletta; Zantonelli, Giulia; Bindi, Alessandra; Cavigli, Edoardo; Moroni, Chiara; Pieralli, Filippo; Fattorini, Caterina; Miele, Vittorio; Bartolucci, Maurizio (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
.